Chronically Honest: An Autoethnographic Paper on the Experiences of a Disabled Librarian - Nikki Andersen (In the Library with the Lead Pipe, 2024)
In Brief: Through autoethnographic reflection and examination of theoretical literature, this article explores my experiences of disability while working in the academic library and information science (LIS) field. The article examines the reality of working in the LIS profession with a hidden sensory and physical disability. It explores the cognitive cost of working with a visual impairment and the experiences of being hard of hearing in a service-oriented profession.